If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(6 + -6x) = -210 (6 * 7 + -6x * 7) = -210 (42 + -42x) = -210 Solving 42 + -42x = -210 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + -42x = -210 + -42 Combine like terms: 42 + -42 = 0 0 + -42x = -210 + -42 -42x = -210 + -42 Combine like terms: -210 + -42 = -252 -42x = -252 Divide each side by '-42'. x = 6 Simplifying x = 6
| -2-2(-3)=8 | | 3(3r+9)-2(r-1)= | | 5x-(-2x+4)= | | srx^2-x-1=x+4 | | (5x+6y+3)(5x+6y-3)= | | 7(x-2)9(8x+5)(3x^2-14x-5)=0 | | 3(16x-3y)= | | (x-1)(x^2+11x+18)=0 | | Cos^2x-5cosx=0 | | 5x-3(7x+y)= | | -3-2y=8 | | 7-10-3=31/2 | | 4(3x+1)-7-7=6+5x-2 | | 3(5)-2y=6 | | x(x-8)=-16(x+1) | | 3(3)-2y=6 | | vw=-18 | | -4x+x=-1 | | y=sqrt(2x^2+5-3) | | 17.53+(-2.42)+0.74= | | p=12/q | | 2x-12=x+64 | | 7(y-8)+24=-2(y-6) | | 4*-2+y=0 | | sin(x)=.5 | | x(15x+17)=18 | | 5(4+x)=4(3x-1)-32 | | 4*-1+y=0 | | -2=5x-27 | | (5n-1)-(4n+7)= | | 30b+2b= | | by=ax |